Do greater sage‐grouse exhibit maladaptive habitat selection?. Issue 3 (3rd March 2021) - Pratt, Aaron C.; Beck, Jeffrey L.
Abstract: Maladaptive habitat selection, where animals select habitat with reduced fitness potential or avoid otherwise suitable habitat, exacerbates the threat of population decline for species vulnerable from habitat loss and fragmentation. The greater sage‐grouse ( Centrocercus urophasianus ) is a species of conservation concern for which research has identified scenarios where populations may be under the influence of maladaptive habitat selection. Our objective was to evaluate whether sage‐grouse selected habitat relative to habitat quality (i.e., ability to provide for higher survival or reproductive success), and to identify any habitat characteristics where they were not matching selection with costs and benefits, during the nesting, brood rearing, adult breeding, adult summer, and adult winter seasons. We measured an overall apparent adaptive relationship between habitat selection and survival for brood, adult breeding, and adult winter habitat. There was an overall apparent maladaptive relationship for nest and adult summer survival. Of 25 specific habitat characteristics that influenced sage‐grouse reproductive success or survival, 13 (52%) had an apparent adaptive selection relationship, 10 (40%) had an apparent maladaptive relationship, and 2 (8%) were either inconclusive or not strongly selected. Surprisingly, most (8 of 10) of the habitat characteristics we observed that were selected contrary to apparent costs or benefits were associated with environmental variables (i.e., topography and vegetation). Relative to possible maladaptive selection and anthropogenic disturbance, grouse selected for areas of higher mortality risk near minor roads during the breeding season and grouse did not select for non‐irrigated agricultural disturbance which had lower mortality risk. However, after accounting for the effects of habitat selection on all demographic rates that determine fitness, these apparent maladaptive selection effects were probably not biologically significant. The strongest evidence we observed for maladaptive habitat selection associated with anthropogenic land use was during summer when grouse were selecting for the edge of irrigated hayfields where there was higher mortality risk. To ensure the success of sage‐grouse conservation actions, we encourage further investigation identifying the mechanisms behind observed cases of apparent maladaptive selection or identifying any fitness benefits that grouse are gaining from selecting risky areas.